Autosomal dominant isolated ('uncomplicated') microcephaly. Issue 11 (November 1988) - Merlob, P; Steier, D; Reisner, S H
Abstract : A large family (13 affected members in three generations) is reported in which isolated microcephaly occurred without any other dysmorphic or neurological abnormalities. The family pedigree confirms the autosomal dominant mode of inheritance with incomplete penetrance, including one example of male to male transmission and the occurrence of a non-manifesting heterozygote resulting in a 'skipped generation'. There is considerable variation in the phenotypic expression of autosomal dominant microcephaly. This isolated (uncomplicated) type of microcephaly should be distinguished from other well defined, dominantly inherited forms of microcephaly.